China eyes Japan - Whiting, Allen S. (University of California Press, 1989)
What influence does the history of Japanese aggression in China have on Chinese images of and policies toward Japan today? Is Chinese acrimony and assertiveness toward Japan in the latter 1980s the product of calculated bargaining pressure or compulsive emotional nationalism? And what are the prospects for Sino-Japanese relations: increased political alignment or continued instability and friction? These are among the questions Allen Whiting, a leading scholar of Chinese foreign relations, addresses in this book. Working largely from interviews and from an examination of the Chinese media, Whiting finds that Chinese policy toward Japan embodies an uneasy tension between hostile imagery and pragmatic interest, manifest in increasing tension during the years 1982-1987. He challenges the commonplace assumptions that post-Mao Chinese foreign policy is pragmatically determined by economic and strategic calculations. Instead, Whiting argues that Sino-Japanese relations are vulnerable to Chinese images based on bitter memories of Japanese aggression combined with misperceptions of Japanese politics and society as well as provocative remarks by Japanese officials. These images are transmitted to younger generations by Chinese mass media with little challenge from more informed governmental and academic specialists. He concludes that, although there is an increased sophistication in the Chinese understanding of the United States and the Soviet Union, this is not yet evident in the case of Japan.